PENGARUH UKURAN PARTIKEL TEMPURUNG SAWIT DAN TEKANAN KEMPA TERHADAP KUALITAS BIOBRIKET - Djoko Purwanto (BRIN Publishing, 2015)
The palm oil industry in the capacity of 100 thousand tons of raw material per year will produce about six thousand tons of palm shell waste. The solid waste is not optimal unutilized as fuel boiler and pavers around the factory. This study aims to get quality palm shell biobriquettes from of treatment particle size palm shell and hydrolic pressure. Procedure research include: natural drying palm shell, crushing of palm shell, powder filtering, mixing with 5% starch solution, printing and pressing, drying naturally biobriquettes, and analysis biobriquettes quality. The treatments used are palm shell particle size which includes 7 mesh, 16 mesh, 25 mesh, and the pressure hydrolic covering 3 tons, 5 tons, 7 tons. Each treatment was replicated three times. The parameters tested include: moisture content, ash content, calorific value, carbon content, volatile matter content, density and compressive strength. The result research: moisture content is between 4.15 - 9.06%; ash content is between 1.68 - 6.19%; the carbon content is between 7.57 - 19.55%; volatile matter content is between 70.49 - 81.95%; sulfur content of all negative; calorific value is between 4218.17 - 4442.34 cal/g; density is between 0.69 - 0.87g/cm³; and compressive strength is between 0.26 - 5.36 kg/cm².